173k views
0 votes
Which equation is equivalent to y – 6 = –12(x + 4)?

A. y = –6x – 48
B. y = 6x – 48
C. y = –12x – 42
D. y = –12x – 54

2 Answers

2 votes

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️


y - 6 = - 12(x + 4)


y - 6 = - 12x - 48

Add sides 6


y - 6 + 6 = - 12x - 48 + 6


y = - 12x - 42

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️

The correct answer is (( C )) .

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️

User Sagar Adhikari
by
5.0k points
1 vote

Answer:

Y-6 = -12 (x+4) Y = -12x - 48 + 6 Y = -12x - 42 answer is c

User Xion
by
5.4k points